2013
DOI: 10.4274/haseki.929
|View full text |Cite
|
Sign up to set email alerts
|

Benign Endikasyonlu Olgularda Histerektomi Yöntemlerinin Karşılaştırılması

Abstract: ÖzetAmaç: Günümüzde benign uterin patolojiler için abdominal histerektomi (AH), vajinal histerektomiden (VH) fazla yapılmaktadır. Total laparoskopik histerektomi (TLH) ise her iki yönteme nazaran daha kısa iyileşme süresi ve günlük hayata dönüşün hızlı olması nedeniyle daha yaygın yapılmaya başlanmıştır. Biz bu çalışmada kliniğimizde yapılan AH, VH ve TLH'ların sonuçlarını karşılaştırdık. Yöntem: Bu çalışmada Bağcılar EAH Kadın Doğum Kliniği'nde 2010 Aralık-2011 Aralık tarihleri arasında benign nedenlerle hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Süer et al (8) included 312 hysterectomy cases and found that in the vaginal hysterectomy group, age, gravidity, and parity were significantly higher than the other groups. Similarly, Sağlam et al (9) included 245 hysterectomy cases and found that gravidity and parity values of the vaginal hysterectomy group were significantly higher than the abdominal hysterectomy group.…”
Section: Discussionmentioning
confidence: 95%
“…Süer et al (8) included 312 hysterectomy cases and found that in the vaginal hysterectomy group, age, gravidity, and parity were significantly higher than the other groups. Similarly, Sağlam et al (9) included 245 hysterectomy cases and found that gravidity and parity values of the vaginal hysterectomy group were significantly higher than the abdominal hysterectomy group.…”
Section: Discussionmentioning
confidence: 95%